Team Assisted Individualization Model Assisted by Effective Ludo Media Improving Student Learning Outcomes - Wilujeng, Donna Restu; Sukamto, Sukamto; Eka Subekti, Ervina (Universitas Pendidikan Ganesha, 2020)
The low competence of mathematical knowledge caused by the lack optimal use of the learning model makes it difficult for students to understand the learning material. The purpose of this study was to analyze the effectiveness of the Team Assisted Individualization model assisted by Ludo media on learning outcomes in terms of the problem-solving ability of fraction material. This type of research was a quantitative study using pre-experimental design in the form of a one-group pretest-posttest design. The number of samples in this study was all students of class IV, amounting to 26 students using saturated sampling type sampling. Data collection in this study was obtained through interviews, tests and documentation. The results of data analysis obtained tcount 9.698 and ttable 1.706 with a significant level of 5%. Because t_count> ttable is 9.698> 1.706, so H_0 is rejected, which means that there are differences in pretest and posttest learning outcomes. Then the two-party t-test of problem-solving abilities shows that tcount> ttable is 8,000> 1,671 then H_0 is rejected, so there is a significant difference in learning outcomes seen from the problem-solving ability using the Team Assisted Individualization model with groups that are taught with conventional models in grade IV SD. The Team Assisted Individualization model assisted by Ludo media is effectively applied in the learning process to improve student learning outcomes for fractions.